A review on machine learning-based models for lane-changing behavior prediction and recognition - David, Ruth; Söffker, Dirk (Frontiers in Future Transportation, 2023)
A major aspect in the development of Advanced Driving Assistance System (ADAS) is the research in developing human driving behavior prediction and recognition models. Recent contributions focus on developing these models for estimating different driving behaviors like lane or speed change. Thus, the models are incorporated into the ADAS to generate warnings and hints for safe maneuvers. Driving behavior recognition and prediction models are generally developed based on Machine Learning algorithms (ML) and are proven to generate accurate estimations. Previous review research contributions tend to focus ML-based models for the prediction and recognition of speed change, trajectory change, and even driving styles. Due to high number of driving errors occurring during a lane change, a state-of-art review of different ML-based models for lane changing behavior prediction and recognition is helpful to present a comparison between different models in terms of structure, influencing input variables, and performance. This enables the integration of the most efficient model for the development of ADAS to avoid accidents during a lane change. First, definitions and terms related the model's task and evaluation metrics used to evaluate the model's performance are described to improve the readability. Then, the different input variables of the models affecting the lane changing behaviors are presented. Next, a review of the models developed based on well-known approaches such as Artificial Neural Network (ANN), Hidden Markov Model (HMM), and Support Vector Machine (SVM) using different input variables is given. Three lane changing behaviors are focused here: left /right lane change and lane keeping. The advantages and disadvantages of the different ML models with a comparison are summarized as well. Finally, the improvements required in the future are discussed.